Iodine-Pseudohalogen Ionic Liquid-Based Electrolytes for Quasi-Solid-State Dye-Sensitized Solar Cells - Lennert, Annkatrin; Sternberg, Michelle; Meyer, Karsten; Costa, Ruben Dario; Guldi, Dirk Michael (ACS Applied Materials and Interfaces, 2017)
In the current work, novel symmetrically alkyl-substituted imidazolium-based ionic liquids have been synthesized featuring either iodide (I-) or selenocyanate (SeCN-) as counteranions. Physicochemical assays based on spectroscopy and electrochemistry techniques have been performed to identify the best ionic liquid for application as electrolytes in quasi-solid-state dye-sensitized solar cells (qssDSSC). The latter were mixed with additives such as 4-tert-butylpyridine (4tbpy) and guanidinium thiocyanate (GuSCN) to optimize electrode surface coverage, ionic diffusion, and dye regeneration. In addition, we demonstrate that electrolytes containing a mixture of I2 and (SeCN)2 enhance the open-circuit voltage of the final quasi-solid-state device by up to 70 mV. As such, iodine-pseudohalogen electrolytes reveal in qssDSSCs a good balance between dye regeneration and hole transport and, in turn, enhance the overall solar energy conversion efficiency by 70% with respect to reference qssDSSCs with iodine-based electrolytes. Finally, devices with the iodine-pseudohalogen electrolyte show a 1000 h stable efficiency of 7-8% under outdoor temperature operation conditions and 1 sun illumination.
EAM Import::2019-03-13